Through the Looking-Glass: Investment Transparency of Canadian Foundations - Wilson, Melissa; Phillips, Susan D. (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale)

(untitled) (SFU Canadian Institute for Studies in Publishing, 2025)
Foundations are under increased scrutiny as to the source, investment, and use of their assets. Although disclosure of total assets and disbursements is mandatory in many countries, information on investment portfolios is not required and, historically, foundations have rarely volunteered suchninformation. However, the rise of trust-based philanthropy and interest in impact and responsible investing encourage greater voluntary investment transparency. This article examines the current state of investment transparency among Canadian foundations, which collectively hold over $135 billion in long-term investment portfolios. Through interviews with foundation leaders, it explores the perceived benefits and barriers to investment transparency, and the factors that support or inhibit greater openness. While the findings indicate that Canadian foundations value transparency in general, voluntary disclosure on investments is limited due to a variety of risk factors and the lack of demand from stakeholders or the public. The study also points to emerging trends that are raising expectations for greater investment transparency by foundations.